APPLICATION AND EVALUATION OF THE ECOLOGICAL PSYCHOLOGY APPROACH TO INSTRUCTIONAL DESIGN (EPAID) - Effken, Judith; McEwen, Marylyn; Vincent, Deborah; Shea, Kimberly; Garcia-Smith, Dianna; Kang, Youngmi; Young, Michael (Online Learning, 2009)
Teaching online can be particularly challenging when there is a need to immerse students located anywhere in the world in specific environmental contexts. We used the Ecological Psychology Approach to Instructional Design (EPAID) to design four courses in two concentration areas (Border Health, and Workforce and Healthcare Delivery Environments). In each case, we sought to provide students with a virtual first-hand understanding of contexts that they would not experience themselves. In this paper, we describe the major tenets of EPAID, the strategies we used to apply EPAID in the courses, and the results of our initial, formative evaluation.